Sulfated polysaccharides from pacific abalone attenuated DSS-induced acute and chronic ulcerative colitis in mice via regulating intestinal micro-ecology and the NF-κB pathway. Issue 22 (20th October 2021) - Jia, Jinhui; Zhang, Panpan; Zhang, Chenxi; Jiang, Guoping; Zheng, Weiyun; Song, Shuang; Ai, Chunqing
Abstract : Due to potential side effects of current drugs in colitis treatment, polysaccharides with anti-inflammatory activities can be considered as alternative molecules for colitis treatment. Abstract : Due to potential side effects of current drugs in colitis treatment, polysaccharides with anti-inflammatory activities can be considered as alternative molecules for colitis treatment. Sulfated polysaccharide from pacific abalone (AGSP) reduced the level of lipopolysaccharides (LPS) and increased the production of short chain fatty acids in the colon of mice, and it reduced the levels of interleukin (IL)-6, IL-1β and tumor necrosis factor (TNF)-α and increased the IL-10 level in in vitro cell models, suggesting that it can be used as a probiotic agent to inhibit intestinal inflammation. Furthermore, AGSP reduced the disease activity index and intestinal damage, improved the mucosal immune response, and inhibited oxidative damage in mice with DSS-induced acute and chronic colitis, which can be associated with modulation of the NF-κB signaling pathway and gut microbiota. AGSP regulated the structure of the gut microbiota and reduced the level of Bacteroides that had positive correlation with the colitis symptoms. The in vitro result showed that AGSP may inhibit mucin degradation by Bacteroides via the change of the polysaccharide utilization strategy, which can protect intestinal barrier integrity. This study is useful to understand the mechanism by which AGSP ameliorates colitis and related diseases and promotes further development of AGSP.